SISTEM INFORMASI AKUNTANSI ATAS PENGENDALIAN PERSEDIAAN PADA REJEKI 2 SWALAYAN DI OMBEN SAMPANG - Mafrudah, Ana; Sakdiyah, Halimatus (Journal of Accounting and Financial Issue (JAFIS), 2023)
This study aims to determine the accounting information system for inventory control at Rejeki 2 Swalayan in Omben Sampang. The type of research used is descriptive qualitative where the aim is to describe systematically the accounting information system for controlling merchandise inventory. Data were collected by means of observation, interview, documentation. The results showed that the accounting information system for inventory control owned by Rejeki 2 supermarkets in Omben Sampang was good. However, there are also weaknesses in the system, namely not using ledgers and auxiliary books. use ledgers and subsidiary books to facilitate transactions. Keywords: Accounting Information Systems and Inventory Control